APPLICATION OF SCRAMBLE MODEL IN IMPROVING BEGINNING READING ABILITY OF GRADE 1 STUDENTS OF ELEMENTARY SCHOOL JEUMPET ACEH BESAR - Huddin, Musfia; Safiah, Intan; Hasniyati, Hasniyati (Elementary Education Research, 2025)
Reading is an important key in the learning process, lack of reading ability is a problem in this study. Students still stutter when reading, when students are asked to read some simple sentences presented by the teacher in front of the class, students need quite a long time to read and are not fluent. The problem in this study is "How are the activities of teachers and students in improving early reading skills using the scramble learning model and how are the results of the early reading skills of class I students of SDN 1 Jeumpet Aceh Besar". The purpose of this study is to improve the early reading skills of class 1 students of SDN 1 Jeumpet Aceh Besar through the scramble model. This type of research is Classroom Action Research which is carried out cyclically, with research subjects consisting of 7 male students and 5 female students. Data collection techniques in this study used tests and observations. Tests are used to see the improvement of students' early reading skills and observations are used to see student activities in the learning process and teacher activities in managing learning through the scramble model. The results of this study indicate that the application of the scramble model can improve students' early reading skills. The increase in value in cycle I has not met the target, only reaching 73.75%, then increasing in cycle II to reach completion of 83.33%. Based on the results of the study, it can be concluded that through the scramble model, it can improve the ability to read early.